Monitoring and managing Microsoft Exchange server 2003 - Daugherty, Mike. (Amsterdam ; Boston : Elsevier Digital Press, 2004)
This authoritative book teaches IT professionals responsible for Exchange messaging systems how to efficiently manage the program's many and complex system capabilities and features. Once you've designed and implemented a messaging system, the bulk of the day-to-day work involves monitoring to ensure an optimum traffic flow, accomplished by continuously reviewing and fine-tuning dozens of system specifications and components. Monitoring and Managing Microsoft Exchange 2003 teaches readers proven and innovative techniques, tools, and procedures for managing and optimizing systems of all sizes and types built on Exchange 2003. Based on the author's own twenty years of messaging system experience and the collective experience of HP, the leading implementer of Exchange Server systems, this book will be a leading resource for Exchange administrators and designers. *Provides best practices and innovative everyday techniques for managing the enterprise Exchange environment *Teaches readers proven procedures for managing and optimizing systems of all sizes and types *Based on the author's own twenty years of messaging system experience.
Chapter 1 Introduction -- Chapter 2 -- Preparing to Manage Exchange 2003 -- Chapter 3 -- Operations Frameworks -- Chapter 4 -- Management and Monitoring Tools -- Chapter 5 -- Managing the Exchange Organization -- Chapter 6 -- Managing Exchange Servers -- Chapter 7 -- Managing E-mail Connectivity Environments -- Chapter 8 -- Managing Recipients -- Chapter 9 -- Addresses, Address Lists, and Offline Address Lists -- Chapter 10 -- Backup and Recovery Operations -- Chapter 11 -- Virus and SPAM Protection -- Chapter 12 -- Monitoring Exchange -- Chapter 13 -- Microsoft Operations Manager -- Chapter 14 -- Proactive Administration Summary.
Includes index.
Keywords: Microsoft Exchange server; Client/server computing; Electronic books